Internal Subdivisions of the Marmoset Claustrum Complex: Identification by Myeloarchitectural Features and High Field Strength Imaging - Pham, Xiuxian; Wright, David K.; Atapour, Nafiseh; Chan, Jonathan M.-H.; Watkins, Kirsty J.; Worthy, Katrina H.; Rosa, Marcello; Reichelt, Amy; Reser, David H. (Frontiers in Neuroanatomy, 2019)
There has been a surge of interest in the structure and function of the mammalian claustrum in recent years. However, most anatomical and physiological studies treat the claustrum as a relatively homogenous structure. Relatively little attention has been directed toward possible compartmentalization of the claustrum complex into anatomical subdivisions, and how this compartmentalization is reflected in claustrum connections with other brain structures. In this study, we examined the cyto- and myelo-architecture of the claustrum of the common marmoset (Callithrix jacchus), to determine whether the claustrum contains internal anatomical structures or compartments, which could facilitate studies focused on understanding its role in brain function. NeuN, Nissl, calbindin, parvalbumin, and myelin-stained sections from eight adult marmosets were studied using light microscopy and serial reconstruction to identify potential internal compartments. Ultra high resolution (9.4T) post-mortem magnetic resonance imaging was employed to identify tractographic differences between identified claustrum subcompartments by diffusion-weighted tractography. Our results indicate that the classically defined marmoset claustrum includes at least two major subdivisions, which correspond to the dorsal endopiriform and insular claustrum nuclei, as described in other species, and that the dorsal endopiriform nucleus (DEnD) contains architecturally distinct compartments. Furthermore, the dorsal subdivision of the DEnD is tractographically distinguishable from the insular claustrum with respect to cortical connections.